This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 3 F ( n ) − F ( n ) = 2 F ( n ) = 3 n +1 − 3 . Now, to verify that this is correct, use mathematical induction as follows. For the base case, F (1) = 3 = 3 2 − 3 2 . The induction hypothesis is that ∑ n − 1 i =1 = (3 n − 3) / 2 . So, n X i =1 3 i = n − 1 X i =1 3 i + 3 n = 3 n − 3 2 + 3 n = 3 n +1 − 3 2 . Thus, the theorem is proved by mathematical induction....
View
Full
Document
This note was uploaded on 12/27/2011 for the course MAP 2302 taught by Professor Bell,d during the Fall '08 term at UNF.
 Fall '08
 BELL,D

Click to edit the document details